Justiça do trabalho : entre a lei e a realidade (1941-1945) - Bartmann, Tatiane (2014)
The following research aims to analyze the relationships of labor in the founding companies of Centro da Indústria Fabril do Rio Grande do Sul (Cinfa) and the mediator role of the Labor Court reconciling or judging labor suits claimed by employees of these establishments. The investigation occurred by analyzing labor cases brought forward by individual employees that were, at the time, analyzed at the 1ª Junta de Conciliação e Julgamento de Porto Alegre (1ª JCJ - the first instance of court regarding labor law) since the year of its opening (1941) until the end of the Estado Novo (1945). Therefore, it addresses the starting period of the organization and functioning of the JT, a type of managed court of labor law that is provided certain autonomy due to having ties to the Executive Power. Following the methodology of content analysis, the individual lawsuits brought by workers against the founding industries of the business association were sorted and grouped into categories divided by themes through the analysis of the complaints of the employees. By doing so, four categories were elaborated: "Contract Termination", "Disciplinary Suspension", "Working Conditions" and "Salary Reduction". From the analysis of these categories, the most frequent complaints made by workers were verified and they, in general, demanded the enforcement of labor legislation comprising laws and justice as a set of codes and legal duties. Thus, it falls to the 1ª JCJ to settle the conflicts between employees and employers by interpreting laws and considering the practical reality of workers, acting between the law and reality.